(untitled) (Euro-Asia Conferences, 2021)
The socio-emotional development of children of preschool age group is considered as one of the topical issues of modern pedagogical and pedagogical psychology. Socialization of preschool children is carried out through communication and consistent interactive activities. In this process, attributes such as accessibility, adaptability, emotionality and emotionality determine the content and level of children’s communication. The article covers the problems related to this issue, the pedagogical and psychological research carried out in this regard and is now carried out in the context of social requirements, as well as recommendations on the role-playing and methods of their application, which are important in the further improvement of socio-emotional development of children of preschool age group